STRATEGI PENGELOLAAN LINGKUNGAN LAUT PADA MASA PANDEMI COVID 19 OLEH DIVERS CLEAN ACTION - Julia Rosemary Tapilatu; Duaitd Kolibongso (Musamus Devotion Journal, 2021)
The issue of marine debris which is dominated by single-use plastic is one of the crucial problems that have the potential to cause various problems in the health of marine and coastal ecosystems, animals, to human health. During the pandemic, this problem continues to increase due to the environmentally unfriendly habits of the community and the lack of effective waste management. Socialization and virtual environmental campaigns are some of the most effective solutions that can increase public awareness in using plastic wisely during pandemic. This fieldwork practice aims to determine the stages of the environmental campaign activity "Plastic Free Parade" and the techniques of delivering materials in a virtual environmental campaign. The fieldwork practice is using a descriptive method that took place during the months of July - September 2020. Retrieval of data and information is obtained through assignments given by the executive director and field supervisor of Divers Clean Action. The practical results show that this activity was attended by 117 communities and 3600 viewers from all regions of Indonesia through zoom and YouTube applications. Various positive responses and commitments were given by the government, society, and other institutions regarding this activity